Postpartum Vascular Dysfunction in the Reduced Uteroplacental Perfusion Model of Preeclampsia. - Lesley Brennan; Jude S Morton; Anita Quon; Sandra T Davidge (PLoS ONE, 2016)
Preeclampsia is a disorder affecting 2-8% of all pregnancies, characterized by gestational hypertension (≥ 140/90 mmHg) and proteinuria (≥300 mg over 24 hours) diagnosed following the 20th week of pregnancy, and for which there is currently no available treatment. While the precise cause of preeclampsia is unknown, placental ischemia/hypoxia resulting from abnormal trophoblast invasion and maternal endothelial dysfunction are central characteristics. Preeclampsia is a major cause of both maternal and fetal morbidity and mortality in the perinatal period. In addition, women who have experienced preeclampsia are more likely to suffer cardiovascular disease later in life. The cause of this elevation in cardiovascular risk postpartum, however, is unknown. We hypothesize that there may be lasting vascular dysfunction following exposure to reduced uteroplacental perfusion during pregnancy that may contribute to increased cardiovascular risk postpartum. Using the rat reduced utero-placental perfusion pressure (RUPP) model of preeclampsia, blood pressure was assessed in dams at gestational day 20, one and three months postpartum. Mesenteric artery and aortic function were assessed using wire myography. We demonstrated hypertension and increased mesenteric artery responses to phenylephrine at gestational day 20, with the latter due to a decreased contribution of nitric oxide without any change in methylcholine-induced relaxation. At one month postpartum, we demonstrated a small but significant vasoconstrictive phenotype that was due to an underlying loss of basal nitric oxide contribution. At three months postpartum, endothelium-dependent relaxation of the aorta demonstrated sensitivity to oxLDL and mesenteric arteries demonstrated decreased nitric oxide bioavailability with impaired methylcholine-induced relaxation; indicative of an early development of endothelial dysfunction. In summary, we have demonstrated impaired vascular function following exposure to a RUPP pregnancy that continued into the postpartum period; suggesting that a pregnancy complicated by preeclampsia may predispose women to later life cardiovascular disease via ongoing vascular dysfunction.